Emotional Intelligence Among Nurses In A Hospital, Kathmandu - Sharma, Poojan; Sapkota, Shraddha (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Emotional intelligence is the capacity to be aware of, and express one’s emotions, and to handle interpersonal relationships thoughtfully and compassionately. Emotional intelligence greatly impacts the nurses’ work. Thus the study aimed to assess the nurses’ emotional intelligence and association with their socio-demographic and work related characteristics. Method: Descriptive cross-sectional study design was used. Nurses of Manmohan Memorial Teaching Hospitals were the study population. Probability stratified proportionate sampling technique was used with sample size 114. Statistical Package for the Social Science was used for data processing and analysis. Schutte Self Report Emotional Intelligence Test was used to identify emotional intelligence. Descriptive and inferential statistics was used for the analysis. Ethical approval was taken from NEHCO IRC. Results: Out of 114 participants, 55.3% were of aged 25 years. Nurses with high level of emotional intelligence were 57.9%. The highest mean percentage of 29.57% was in perception of emotion followed by managing own emotion with the mean percentage of 27.82%. The each subscales of emotional intelligence scale had moderate positive correlation with other subscales. There was no any significant association of emotional intelligence with socio-demographic and work related characteristics of nurses. Conclusion: More than half of the nurses had high level intelligence, the highest man percentage was on perception of emotion. No any nurses’ characteristic under study was associated with their emotional intelligence.